Immunologic Pathways That Predict Mortality in HIV-Infected Ugandans Initiating Antiretroviral Therapy. (1st March 2017) - Lee, Sulggi; Byakwaga, Helen; Boum, Yap; Burdo, Tricia H.; Williams, Kenneth C.; Lederman, Michael M.; Huang, Yong; Tracy, Russell P.; Cao, Huyen; Haberer, Jessica E.; Kembabazi, Annet; Bangsberg, David R.; et al.
Summary: The plasma kynurenine/tryptophan ratio, a marker of adaptive immune defects, remained significantly predictive of mortality, even after adjustment for other T-cell and plasma biomarkers, in human immunodeficiency virus (HIV)–infected Ugandans initiating antiretroviral therapy, suggesting an independent effect on mortality. Abstract: The plasma kynurenine/tryptophan (KT) ratio, a marker of adaptive immune defects, strongly predicts mortality during treated human immunodeficiency virus (HIV) disease in Ugandans as compared to US-based populations. Here, the KT ratio and T-cell and plasma biomarkers of immune activation were measured among 535 HIV-infected Ugandans prior to ART initiation and at month 6 of viral suppression. The month 6 KT ratio (adjusted hazard ratio [aHR], 2.74), soluble CD14 level (aHR, 2.32), interleukin 6 level (aHR, 2.34), and D-dimer level (aHR, 1.95) were associated with mortality occurring ≥6 months after ART initiation. The KT ratio remained significantly predictive of mortality even after adjustment for the additional biomarkers, suggesting an independent contribution to clinical outcomes in resource-limited settings.